Analysis of Communication and Employee Interaction Gap at the UPTD of Namohalu Esiwa Community Health Center In Public Service - Harefa, Tipnov Misericordias; Telaumbanua, Eliagus; Hulu, Fatolosa; Waruwu, Robin Markus Putra (ProBisnis : Jurnal Manajemen, 2025)
Service public is function main government that aims For fulfil need base society , such as health And education . However , the gap communication And interaction between employee And community at the UPTD Puskesmas Namohalu Esiwa Still become significant challenges . Research This aim For analyze factors reason gap communication And interactions , as well as the impact to quality service public . The method used is approach quantitative with design descriptive , involving interview And questionnaire covering 50 employees Health Center . Results study show that burden Work height , lack of training communication , and difference background behind culture as well as Language contribute to gap this . Effort handling carried out including implementation 3S culture ( Smile , Greetings, Greetings ) and utilization technology communication . It is hoped that , with overcome gap communication , quality service can increase And trust public to Community Health Center can awake .